RELATIONSHIP BETWEEN BUDGET SYSTEM EFFICIENCY AND VALUES-BASED PERFORMANCE EVALUATION INDICATORS AT THE SADERAT BANK OF IRAN: A STUDY IN FINANCIAL EDUCATION - Parvizi, Hadi; Jamshidinavid, Babak (Lex humana (Petrópolis, RJ, Brasil), 2021)
The aim of this study was investigating the relationship between the budgeting system efficiency and value-based performance evaluation indicators in Saderat Bank of Iran. The research method is quantitative in terms of data type and it is a descriptive survey in terms of how the research is conducted and an ex-post facto correlational research in terms of the relationship between variables. From the perspective of execution logic, this study can be considered as a deductive-inductive research. The research statistical population comprised the employees of Saderat Bank in Kermanshah Province, amounting to 490 people. A sample size of 216 subjects was selected based on random sampling method and with the help of Cochran's formula for finite population and the research questionnaire rated on a Likert scale was distributed and completed by the research sample and was used in the analysis. Finally, by performing statistical tests using statistical software on the information about the respondents, which included 216 questionnaires completed by the staffof Saderat Bank in Kermanshah Province, it was determined that there is a significant and positive relationship between manpower expertise with economic value-added, market value-added and cash value-added. According to the results, proper management of costs and investments used can improve economic value-added.